Age- and gender-related differences in the structure and the meaning of personal values. (1st February 2019) - Borg, Ingwer
Abstract: Previous research has shown that persons' ratings of the importance of personal values differ for men and women, and also for persons of different age. Differences in the structure and the meaning of values have, however, not been studied systematically. We looked at this question from the perspective of the most established value theory (Schwartz, 1992) and the related PVQ21 scale, using data of the European Social Survey 2012 ( N = 50, 408) and of a recent German survey on crime prevention ( N = 3272). It was found that the structure of personal values remains the typical value circle for all gender and age groups, but this circle and, in particular, the items that measure Schwartz's ten basic values, shift systematically with gender and age, reflecting systematic changes in the perceived meaning of the values.